Immunologic Insights on the Membrane Proximal External Region: A Major Human Immunodeficiency Virus Type-1 Vaccine Target - Molinos-Albert, Luis M.; Clotet, Bonaventura; Blanco, Julià; Carrillo, Jorge (Frontiers in Immunology, 2017)
Broadly neutralizing antibodies (bNAbs) targeting conserved regions within the HIV-1 Envelope glycoprotein (Env) can be generated by the human immune system and their elicitation by vaccination will be a key point to protect against the wide range of viral diversity. The Membrane Proximal External Region (MPER) is a highly conserved region within the Env gp41 subunit, plays a major role in membrane fusion and is targeted by naturally-induced bNAbs. Therefore, the MPER is considered as an attractive vaccine target. However, despite many attempts to design MPER-based immunogens, further study is still needed to understand its structural complexity, its amphiphilic feature and its limited accessibility by steric hindrance. These particular features compromise the development of MPER-specific neutralizing responses during natural infection and limit the number of bNAbs isolated against this region, as compared with other HIV-1 vulnerability sites, and represent additional hurdles for immunogen development. Nevertheless, the analysis of MPER humoral responses elicited during natural infection as well as the MPER bNAbs isolated to date highlight that the human immune system is capable of generating MPER protective antibodies. Here, we discuss the recent advances describing the immunologic and biochemical features that make the MPER a unique HIV-1 vulnerability site, the different strategies to generate MPER-neutralizing antibodies in immunization protocols and point the importance of extending our knowledge towards new MPER epitopes by the isolation of novel monoclonal antibodies. This will be crucial for the redesign of immunogens able to skip non-neutralizing MPER determinants.